Risk Factors for the Musculoskeletal Pain Based on the Computer Ergonomics Related Practices among Medical Professionals: - Abu Saleh Mohammad Mainul Hasan; Md Israt Hasan; Mohammed Emran; Muzahidul Islam, Mollah Mohammad; Tulshi Chandra Saha; MD Abdullah Al Mamun (KYAMC Journal, 2023)
Background: With The fast growing world, in Bangladesh also getting increased usage of digital connectivity has led to a rise in online activities and also rise in the musculoskeletal (MSK) pain among the professionals. Objective: We investigating the relationship between MSK pain and discomfort among resident doctors because of computer ergonomics related issues. Materials and Methods: The study collected computer ergonomics related information from 227 resident doctors who had used computer for at least one year. Along with descriptive statistical tools, this study addressed essential test of hypothesis and administered a binary logistic regression model to identify the risk factors of MSK pain among resident doctors. Results: The prevalence of neck pain and lower back pain was estimated over 50% whereas more than one-third faced pain in one or both eyes as well as in their upper back. The different sorts of ergonomics significantly associated with different types of MSK pain. The faculty type- taking break, awkward posture, the shoulder placement had significant impact on the pain in one or both eyes. Besides, having gap between leg and seat as well as monitor placement were the significant predictor of neck pain. In addition, wrist not straightening was not the only risk factor for lower back pain and faculty type, device type, gap between legs and seat, Not having an armrest were the risk factors for upper back pain. Conclusion: The computer ergonomics related practices are the fundamental codes for the medical professionals to avoid MSK pain and hence specific practice safeguards for specific pains. KYAMC Journal Vol. 14, No. 01, April 2023: 19-24